(203) Outline of Courses on Budget Classification and Management إطار مقرر تصنيف الموازنة وإدارتها - O. Khalid, R. (INP, 2024)
This memorandum presents a comprehensive academic framework for the course “Budget Classification and Management,”. The course is designed to develop both theoretical and practical understanding of public budgeting and its role in economic and social development planning. It is organized into three interrelated parts. The first part examines the organizational requirements and techniques of budget formulation, execution, and control, focusing on the budget cycle, the distribution of responsibilities among government agencies, the functions of departmental and central budget offices, methods of revenue and expenditure estimation, and the importance of coordinating all stages of budgeting to enhance efficiency, reduce waste, and support sound fiscal policy. The second part explores analytical tools used to assess government transactions for development planning purposes. It highlights the transition from traditional government accounts designed primarily for accountability toward policy-oriented accounts capable of measuring the impact of public sector activities on the national economy. Particular attention is given to the economic classification of government transactions, including current and capital expenditures, transfer payments, interest payments, and various forms of public revenue, as well as the classification of government institutions and the application of integrated economic and functional classifications to evaluate expenditure according to both purpose and economic effect. The third part introduces programme and performance budgeting, emphasizing government objectives, programmes, projects, and activities rather than merely the items purchased. It discusses the principles for structuring programmes, measuring outputs and achievements, and assessing performance, while also addressing the administrative, accounting, and statistical challenges associated with implementing this budgeting approach. The memorandum concludes with an extensive reading list comprising leading academic works and United Nations publications on public finance, government accounting, budget classification, and programme and performance budgeting, making it a foundational reference for the study of modern public financial management and development-oriented budgeting systems.